The Leadership Role of Nurse Educators in Mental Health Nursing. (2nd September 2015) - Sayers, Jan; Lopez, Violeta; Howard, Patricia B.; Escott, Phil; Cleary, Michelle
Abstract : Leadership behaviors and actions influence others to act, and leadership in clinical practice is an important mediator influencing patient outcomes and staff satisfaction. Indeed, positive clinical leadership has been positioned as a crucial element for transformation of health care services and has led to the development of the Practice Doctorate Movement in the United States. Nurse educators in health care have a vital leadership role as clinical experts, role models, mentors, change agents, and supporters of quality projects. By enacting these leadership attributes, nurse educators ensure a skilled and confident workforce that is focused on optimizing opportunities for students and graduates to integrate theory and practice in the workplace as well as developing more holistic models of care for the consumer. Nurse educators need to be active in supporting staff and students in health care environments and be visible leaders who can drive policy and practice changes and engage in professional forums, research, and scholarship. Although nurse educators have always been a feature of the nursing workplace, there is a paucity of literature on the role of nurse educators as clinical leaders. This discursive article describes the role and attributes of nurse educators with a focus on their role as leaders in mental health nursing. We argue that embracing the leadership role is fundamental to nurse educators and to influencing consumer-focused care in mental health. We also make recommendations for developing the leadership role of nurse educators and provide considerations for further research such as examining the impact of clinical leaders on client, staff, and organizational outcomes.